Makna dan Nilai Sosial dalam Tradisi Rebo Wekasan di Desa Muaradua: Studi Etnografi tentang Kearifan Lokal dan Kepercayaan Masyarakat - Hikmatullah Hikmatullah; Syifa Nurfadilah; Maulana Hakim Al Fazri; Sabila Khaerani Putri; Rafli Ramdan; Aidil Fitra Lubis (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to explore the meaning and social values embedded in the Rebo Wekasan tradition in Muaradua Village, Lebak Regency, through an ethnographic approach. The Rebo Wekasan ritual, performed on the last Wednesday of Safar, is perceived by the community as a spiritual effort to seek divine protection from misfortune while strengthening social solidarity. Data were collected through participant observation, in-depth interviews with religious and community leaders, and documentation of ritual activities. The findings indicate that this tradition continues to be preserved, particularly through communal gatherings, the performance of the salat tolak bala, collective prayers, and acts of charity. Social values such as togetherness, mutual cooperation, solidarity, harmony, and cultural preservation are strongly reflected throughout the ritual process. Although certain elements such as the practice of writing wafaq are gradually declining due to the loss of tradition bearers, the spiritual and social essence of Rebo Wekasan remains intact through collective community engagement. This study affirms that Rebo Wekasan represents an adaptive and relevant form of local wisdom that helps maintain cultural identity amid societal change.